Coping strategies for domestic violence against pregnant female adolescents: integrative review - Cibele Monteiro Macedo; Paula Orchiucci Miura; Dora Mariela Salcedo Barrientos; Gisele Almeida Lopes; Emiko Yoshikawa Egry
ABSTRACT Objective: To investigate and analyze in the scientific literature coping strategies for domestic violence against pregnant female adolescents. Method: This is an integrative literature review, conducted from July to August 2017 on LILACS, SciELO and PubMed, using the descriptors and the MeSH terms: confrontation, violence, adolescent, pregnant women, prenatal care. Result: The sample comprised 9 articles that were organized and characterized according to year, country of study and coping strategy used. The main forms of coping involved the active search for cases and the primary care approach with all family members. Conclusion: Individualized prenatal care, the change in professional training and networking activities were pointed out as important components of the strategies for coping with violence against pregnant adolescents.